Turbidity effect derived from palm oil mill effluent altered predation period of siamese fighting fish (Betta splendens, Regan 1910) - Ilham Zulfahmi; Agung Setia Batubara; Adli Waliul Perdana; Zultira Harina Roza; Badratun Nafis; Furqan Maghfiriadi (Depik, 2023)
Contamination of palm oil mill effluent (POME) into water bodies potentially increases turbidity, resulting in disrupting aquatic organisms behaviour, including predation period. However, the effect of increased turbidity due to POME contamination toward the fish predation is still unexplored. Siamese fighting fish (Betta splendens) is one of the ideal test fish to investigate this effect. This study aims to analyze the effect of increased turbidity due to POME contamination toward the fish predation period of Siamese fighting fish. The research design was completely randomized with six treatments (0, 20, 40, 60, 80 and 100 NTU) followed by five repetitions for each treatment. The experimental data parameters include the predation rate of Siamese fighting fish during foraging activity, which was calculated from the percentage of the number of mosquito larvae consumed per 2 min during 15 min. The significance level of predation between treatments in each observation time period was analyzed using a one-way Analysis of Variance (ANOVA) with the confidence interval set at the 95% level. The results showed that at a turbidity level of 100 NTU, the predation period of Siamese fighting fish had been altered. In the period of 0-2 min, the predation rate decreased significantly. Meanwhile, the predation rate increased significantly during the period of 2-4 and 8-10 min. This finding should be considered to support POME remediation management, especially turbidity parameters.Keywords:POMEFeeding periodForaging areaTurbidity